Evaluating the Efficacy of a 5‐Min Music Listening Intervention for State Anxiety Reduction in College Students: A Randomized Controlled Trial - Jameel Soqia; Laila Yakoub‐Agha; Mohammad Basheer Alameer; Lujain Nahas; Lama Mohamad; Ibrahim Antoun; Caroline Almohsen; Samer Mohsen (Health Science Reports)
ABSTRACT Objective The primary objective of this research was to investigate the impact of a brief 5‐min period of listening to a standardized piece of music (Oriental Jazz) on state anxiety among Syrian college students, providing insights into the potential effectiveness of music as a pre‐lecture anxiety reduction tool. Methods A two‐phase randomized controlled trial conducted in Damascus, Syria. The participants were college students aged 18–24 who met specific criteria and were randomly assigned to either a music intervention group or a control group. State anxiety was measured pre‐ and post‐intervention using the spielberger state anxiety inventory (STAI‐S). Results In total, 69 participants were included in this study. The mean score decreased non‐significantly in the intervention group (37.9–36.8, p = 0.258) and the control group (46–43.6, p = 0.444). The changes in the anxiety score on phase 2 were insignificant between both study arms (p = 0.622). These results indicate that music has no significant effect on STAI scores. Conclusion Our study did not find evidence supporting the anxiety‐reducing effects of a brief exposure to a unified piece of music (Oriental Jazz). Given these findings, this intervention does not appear to have benefits for reducing anxiety when applied before lectures. Future investigations should consider personalized music interventions, duration, and individual preferences.